Abundance, Diversity, and Depth Distribution of Planctomycetes in Acidic Northern Wetlands - Dedysh, Svetlana N.; Ivanova, Anastasia O. (Frontiers in Microbiology, 2012)
Members of the bacterial phylum Planctomycetes inhabit various aquatic and terrestrial environments. In this study, fluorescence in situ hybridization (FISH) was applied to assess the abundance and depth distribution of these bacteria in nine different acidic wetlands of Northern Russia. Planctomycetes were most abundant in the oxic part of the wetland profiles. The respective cell numbers were in the range 1.1–6.7 × 107 cells g−1 of wet peat, comprising 2–14% of total bacterial cells, and displaying linear correlation to the peat water pH. Most peatland sites showed a sharp decline of planctomycete abundance with depth, while in two particular sites this decline was followed by a second population maximum in an anoxic part of the bog profile. Oxic peat layers were dominated by representatives of the Isosphaera–Singulisphaera group, while anoxic peat was inhabited mostly by Zavarzinella- and Pirellula-like planctomycetes. Phylogenetically related bacteria of the candidate division OP3 were detected in both oxic and anoxic peat layers with cell densities of 0.6–4.6 × 106 cells g−1 of wet peat.